Cytostatic activity of antiviral acyclic nucleoside phosphonates in rodent lymphocytes - Zídek, Zdenek; Potmesil, Petr; Holý, Antonín (Toxicology and applied pharmacology, 2003)
Acyclic nucleoside phosphonates (ANPs) inhibit replication of both DNA viruses and retroviruses, including HIV. The major mechanism of their antiviral action is inhibition of virus-induced DNA polymerases and/or of reverse transcriptases. We investigated the effects of ANPs on proliferation of mitogen-stimulated mouse and rat splenocytes. Included in the study were compounds differing at the heterocyclic base, i.e., adenine (A) and 2,6-diaminopurine (DAP), and at the N(9)-side chain, i.e., 9-[2-(phosphonomethoxy)ethyl] (PME) and (R)- or (S)-enantiomers of 9-[2-(phosphonomethoxy)propyl] (PMP) moieties, and their numerous N(6)-substituted derivatives. The medial inhibitory concentrations (IC50) of N(6)-nonsubstituted compounds range from 0.13 (PMEDAP) to 354 microM ((R)-PMPA). Antiproliferative effects are more pronounced in PME than in PMP series, and they are more prominent in DAP compared to A analogs. The (S)-enantiomers of PMP series are more effective than corresponding (R)-congers. The highest cytostatic potential is exhibited by N(6)-allyl-PMEDAP (IC50 = 0.017 microM) and N(6)-cyclopropyl-PMEDAP (IC50 = 0.036 microM). The N(6)-substituted derivatives of (S)-PMPA are virtually devoid of cytostatic activity. No tight correlation between the cytostatic and reported antiviral effects could be detected.
Keywords: buněčné dělení; Animals; Antiviral Agents; potkani inbrední LEW; vztah mezi dávkou a účinkem léčiva; Female; lymfocyty; Inhibitory Concentration 50; Adenine; antivirové látky; interleukin-10; ženské pohlaví; Organophosphorus Compounds; Tenofovir; interleukin-2; Nucleosides; Structure-Activity Relationship; Antineoplastic Agents; Mice; protinádorové látky; inhibiční koncentrace 50; Interleukin-2; organofosforové sloučeniny; nukleosidy; kultivované buňky; myši; Interleukin-10; Cells, Cultured; organofosfonáty; Dose-Response Relationship, Drug; adenin; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; Lymphocytes; tenofovir; Cell Survival; zvířata; viabilita buněk; Mice, Inbred C57BL; Cell Division; Rats, Inbred Lew; Rats; Organophosphonates; myši inbrední C57BL